Análise histológica e morfométrica dos efeitos do uso de alendronato de sódio na reparação óssea de defeitos críticos em crânio de coelhos - Menuci Neto, Angelo (2009)
Dentistry has a challenge to rehabilitate the partial and total edentulism that affects a large number of patients. Among the treatment options, dental implants play an important role. Once osseointegration demands bone volume to assure long lasting results, frequently alveolar bone reconstruction is needed. Autogenous bone is considered the gold standard material to substitute the bone lost due to its biocompatibility and previsibility, but commonly it loses graft volume in the healing period by osteoclast mediated bone resorption. In this study the use of sodium alendronate, a potent inhibitor of the osteoclast, as a therapeutic option to reduce bone lost after bone graft reconstruction was tested. Thirty two white New Zealand adult male rabbits, weighting from 3 to 4kg under the Brazilian College of Animal Experimentation (COBEA) guidelines to animal experimental were used, in the USC bioterium. Critical defects with 11 diameter width in the parietal bone to the dura mater deep were done. The left defects were filled with autogenous bone graft and the right side defects were filled with blood clot. The test group received sodium alendronate once a week and the control group received no medication, during the 7, 14, 30 and 60 days experimental period. The test groups present a better bone formation in the 14 and 30-days post surgery, demonstrating an acceleration of the healing process when compared with the control groups, show no statistical difference between the test and control groups regarding to bone formation at the end of the study (60 days). We suggest more studies with larger specimens to define more precisely the indication of this drug as a feasible way to prevent autogenous bone graft losses.